Interplay between Elastic and Electrochemical Properties during Active Material Transitions and Aging of a Lithium‐Ion Battery. Issue 4 (13th February 2023) - Feiler, Simon; Daubinger, Philip; Gold, Lukas; Hartmann, Sarah; Giffin, Guinevere A.
Abstract: The interplay between the internal mechanical properties and external mechanical conditions of a battery cell, e. g., Young's modulus and thickness change, has a crucial impact on the cell performance and lifetime, and thus, needs to be fully understood. In this work, 12 Ah lithium‐ion battery pouch cells were studied during cycling and aging by non‐invasive operando ultrasonic and dilation measurements. The effective Young's modulus increases and the thickness varies the most within a single cycle during the graphite transition from stage 1L to 4, at the beginning of the 2 to 1 stage transition and at the phase transition of the nickel‐rich NCM from H2 to H3. After 1000 cycles of aging, the overall effective Young's modulus of the lithium‐ion battery decreases by ∼11 %–12 % and the cell thickness increases irreversibly by ∼3 %–4 %, which is mostly related to a thicker and possibly softer, more porous solid electrolyte interphase layer. Abstract : Revealing the changes of mechanical property : The overall effective Young's modulus of the lithium‐ion battery, measured by ultrasonic time of flight and dilation measurements, decreases by ∼11 %–12 % over the course of 1000 cycles. The link between the mechano‐acoustic properties and stage transitions of the electrode materials has been demonstrated.